Role Modeling and Reasons: Developmental and Normative Grounds of Moral Virtues - Audi, Robert (Journal of moral philosophy, 2017)
It is uncontroversial that virtues and reasons are connected. But moral theorists differ widely regarding just what the connections are, and so far there has not been a fully adequate response to the question whether, in some important way, the category of reasons is more basic than that of virtues. This paper pursues that question. It begins with developmental considerations concerning what constitutes role modeling of the kind that best contributes to virtue. In this context, it explores what is required for a proper “aretaic” responsiveness to such role modeling. Reasons for action are shown to play an essential role in such responsiveness. The paper also shows that we cannot adequately understand virtues apart from appeal to the kinds of normatively significant reasons that must figure in their characteristic exercises. The paper connects this conclusion with epistemological points, such as those indicating how one can know that a person has a virtue, with ontological points concerning what psychological properties ground virtues, and with developmental points indicating how virtue must apparently be role modeled if it is to be (demonstratively) well taught. None of the emerging conclusions implies that virtues are of secondary importance in ethics, nor even that, apart from virtue, human beings can be expected to act morally with reliable steadfastness. Whether or not virtues are fundamental in one or another philosophically interesting way, they appear to be psychologically real traits of persons and both morally and intellectually indispensable.